Desafios do ensino jurídico na pós-modernidade: da sociedade agrícola e industrial para a sociedade da informação - Silva, Daniel Pereira Militão da (2009)
This work aims to examine the new demands that the Brazilian legal education is facing in the present time, called post-modern, which groups a series of structural transformation and changes that has occurred in world society, especially after the second world war. From a philosophical and historical perspective, we start from the hypothesis that Post-modernity brings along with itself new demands for Brazilian legal education and represents a challenging time to encourage reflection on the meaning and the role of this courses in this new scenario. The route starts from the description, in the first chapter of the characteristics of Post modernity, for then examine the proposals of the State, expressed in the curriculum, over the almost 200 years of legal courses, with particular attention to new prospects opened with the 1988 Federal Constitution. The more specific examination of new skills and competencies required for legal courses and students in the context of Post modernity performed in this work points to the necessity of a change of the existing paradigms in the formation of future lawyers, highlighting in particular the adoption of interdisciplinarity as formative proposal. We concluded that the great change, nevertheless, resides in the construction of a new conception on the teaching of the Right, a new mentality, which process must implicate the whole society, as well as the perception of the new forms of professional acting, when the passivity and the excessive litigiousness are surpassed, in order to value other forms of resolution and prevention of conflicts